‘E-TAP’ CURRICULUM FOR VIRTUE EDUCATION: A FIT ANALYSIS TO THE ‘SKOLA-2030’ CURRICULUM - Fernandez Gonzalez, Manuel Joaquin; Elksne, Gunita; Sidorova, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The virtue education curriculum ‘e-TAP’ is one of the recent efforts for improving character and virtue education at school in Latvia from preschool till grade nine. The objective of this research was to provide evidence regarding whether this curriculum is appropriate (‘fits’) to the Latvian context, in particular in reference to the Skola-2030 curriculum. Based on fit and feasibility theory, this work addressed the research question: “How does the treatment of virtues of the e-TAP curriculum fit to the treatment of virtues of the new Skola-2030 curriculum?”. The analysis used statistical descriptive frequency analysis of the virtues of each programme and comparative analysis between the two document sets included in each of them, using Excel software. The results show that Skola-2030 programme stresses performance and civic virtues, while the e-TAP programme underlines moral and intellectual virtues. Performance virtues are the most important ones in Skola-2030 (38 %), but account only for 17 % in the e-TAP curriculum. In addition, in Skola-2030 curriculum civic virtues account for 23 %, while in e-TAP they are only 8 %. In the e-TAP curriculum, moral virtues account for half of all the mentions (50 %) and intellectual virtues for 25 %, whereas in Skola-2030 those virtue groups account for 22 % and 18 %, respectively. The high ‘complementarity fit’ of both programmes suggests that the e-TAP curriculum could considerably enrich the Skola-2030 educational offer. Suggestions for e-TAP programme improvement and further research are put forward.